2019
DOI: 10.1002/ett.3745
|View full text |Cite
|
Sign up to set email alerts
|

An improved user authentication protocol for wireless sensor networks

Abstract: Wireless sensor networks (WSNs) have its applications in many domains such as agriculture, medicine, safety, and industry. Due to its wireless channel, it is vulnerable to many security threats. To provide end‐to‐end secure communication, various authentication and key agreement protocols have been discussed. Recently, Li et al have designed a mutual authentication and key agreement protocol for WSNs. However, it is found that this scheme does not resist to offline password guessing, device stolen, insider, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Braeken 20 has provided authentication protocol based on physically unclonable function (PUF), but later, its drawbacks were pointed out in the scheme. 21 Li et al 22 presented a lightweight authentication scheme using chaotic maps, but later, Kaur et al 23 showed that the scheme 22 is not secure from offline password guessing attack and insider attack. Recently, many schemes have been proposed for WSNs such as the scheme 24 using physical unclonable function and scheme 25 using ECC for medical environment.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Braeken 20 has provided authentication protocol based on physically unclonable function (PUF), but later, its drawbacks were pointed out in the scheme. 21 Li et al 22 presented a lightweight authentication scheme using chaotic maps, but later, Kaur et al 23 showed that the scheme 22 is not secure from offline password guessing attack and insider attack. Recently, many schemes have been proposed for WSNs such as the scheme 24 using physical unclonable function and scheme 25 using ECC for medical environment.…”
Section: Related Workmentioning
confidence: 99%
“…As WSNs are vulnerable to various attacks such as impersonation attack, insider attack, and replay attack, so these attacks should be considered while developing authentication protocol for WSNs. In the past couple of decades, many user authentication schemes have been proposed, but some attacks such as impersonation attack, insider attack, and replay attack can be prominently found in those schemes 13,15,23,27 . So, there is a need of designing a secure and lightweight authentication protocol for WSNs which is free from these attacks.…”
Section: Introductionmentioning
confidence: 99%
“…The adversary must not be able to link the eavesdropped or recorded login messages to a user. 54 In the proposed protocol, the user uses at least one random parameter/number in all of his/her transmitted messages (such as S 2 in {B 1 , B 2 , B 9 }), and UT i is updated in each session. Therefore, at the end of the protocol, not only the user remains untraceable but also the adversary cannot find a logical resemblance between the messages by eavesdropping or recording the transmitted messages.…”
Section: User Traceability Attackmentioning
confidence: 99%
“…U sends {AID, S, K, T 1 , M 2 } to NCC, and the parameter K is a constant in each session, so A can easily trace U based on this parameter. 41,42…”
Section: User Traceabilitymentioning
confidence: 99%